TIME TO DISCONTINUATION OF SGLT2 INHIBITORS AMONG ADULTS WITH TYPE 2 DIABETES AT UNIVERSITI MALAYA MEDICAL CENTRE - Sofian, Nurul Farhana Mohd; Hamid, Siti Azrin Ab; Kueh, Yee Cheng; Tai, Yi Wern; Lim, Lee-Ling (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have emerged as a new guideline-directed medical therapy (GDMT) for managing cardiovascular-kidneymetabolic (CKM) syndrome. Understanding the pattern of SGLT2i discontinuation can help prevent unwarranted discontinuation of this GDMT and simultaneously develop interventions to mitigate its possible adverse sequelae. We aimed to evaluate the time to discontinuation of SGLT2i based on patient-, clinical- and medication-related factors among adults with type 2 diabetes (T2D) at the Universiti Malaya Medical Centre, Kuala Lumpur, Malaysia. METHODOLOGY We conducted a retrospective cohort study involving adults aged 18 years and above with T2D who were initiated with SGLT2i between January 2016 and December 2021. We used the Kaplan-Meier curves with log-rank tests to estimate the median time to SGLT2i discontinuation. RESULTS A total of 602 adults with T2D were analysed. The overall median time to SGLT2i discontinuation was 40.5 months (95%CI [34.6, 54.0]). Adults with T2D who were on empagliflozin (vs. dapagliflozin; P = 0.041) and concomitant DPP4 inhibitors (P = 0.028) had significantly longer treatment persistence. Additionally, adults with baseline eGFR <60 ml/min/1.73 m2 discontinued SGLT2i earlier than those with baseline eGFR ≥60 ml/min/1.73 m2 (p = 0.002). The overall treatment persistence rates at 6 months, 1 year, 3 years and 5 years were 78.0%, 68.2%, 49.4% and 42.6%, respectively. The top 3 reasons for SGLT2i discontinuation were as follows: 1) high pill burden and nonadherence (15.8%); 2) a decline in eGFR and acute kidney injury (10.3%); and 3) financial constraints (8.4%). CONCLUSION This study provides valuable insights into the time to SGLT2i discontinuation in adults with T2D at an urban academic institution. As SGLT2i are the GDMT for CKM syndrome, the underlying factors behind unwarranted SGLT2i discontinuation should be explored to facilitate more personalized diabetes management to optimize health outcomes.